2017
DOI: 10.1371/journal.pone.0176287
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of long noncoding RNAs as biomarkers in urothelial carcinoma

Abstract: Many long noncoding RNAs (lncRNAs) are deregulated in cancer and contribute to oncogenesis. In urothelial carcinoma (UC), several lncRNAs have been reported to be overexpressed and proposed as biomarkers. As most reports have not been confirmed independently in large tissue sets, we aimed to validate the diagnostic and prognostic value of lncRNA upregulation in independent cohorts of UC patients. Thus, expression of seven lncRNA candidates (GAS5, H19, linc-UBC1, MALAT1, ncRAN, TUG1, UCA1) was measured by RT-qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…Study population RNA-sequencing reads per kilobase million (RPKM) data of patients with BLCA were obtained from TCGA [12,25]. The cohort contained 433 samples, including 414 tumor tissue samples and 19 non-tumor adjacent bladder tissue samples.…”
Section: Methodsmentioning
confidence: 99%
“…Study population RNA-sequencing reads per kilobase million (RPKM) data of patients with BLCA were obtained from TCGA [12,25]. The cohort contained 433 samples, including 414 tumor tissue samples and 19 non-tumor adjacent bladder tissue samples.…”
Section: Methodsmentioning
confidence: 99%
“…The results revealed that the level of TUG1 was significantly higher in MM patients than in healthy volunteers, indicating that TUG1 may play a role in disease progression in MM. Furthermore, it has been observed that higher TUG1 expression levels are associated with the disease state in bladder carcinoma samples . Functional studies have revealed that TUG1 is induced in a p53‐dependent manner, bounds to polycomb repressive complex 2 (PRC2), and plays a role in repressing important cell cycle‐related genes .…”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
“…48 In addition, Nagoshi et al also found that the rearrangement of the PVT1 gene was frequently observed in MM harboring 8q24 rearrangements, which are associated with tumor progression. 51 PVT1 has been reported to be involved in variants t(2;8), t(8;22), or t (8;14) in human Burkitt lymphoma, 52,53 and its overexpression has been responsible for the suppression of apoptosis. 54 Furthermore, several studies have reported the breakpoints within a region centromeric to PVT1, suggesting that PVT1 is one of the target genes of rearrangement that may play a role in driving MM.…”
Section: Pvt1mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, circRNAs regulate malignant behaviors of cancer cells, such as proliferation, apoptosis resistance, migration, invasion and drug resistance 14,15 . Although several circRNAs have been reported to participate in the tumorigenesis and progression of HCC [16][17][18] , the expressions and roles of circRNA in chemoresistance of HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%